2021
DOI: 10.31219/osf.io/hqkju
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Conspiracy Theories: A Cultural Evolution Theory approach

Abstract: Conspiracy theories have been part of human culture for hundreds of years, if not millennia, and have been the subject of research in academic fields such as Social Psychology, Political Science and Cultural Studies. At present, there has been little research examining conspiracy theories from a Cultural Evolution perspective. This chapter discusses the value of Cultural Evolution approaches to understanding the diffusion of conspiracy theories. Focusing on the role of biases in cultural transmission, it argue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 121 publications
0
4
0
Order By: Relevance
“…This has been demonstrated experimentally using micro-society designs (Blaine & Boyer, 2018;Moussaïd et al, 2015;Stubbersfield et al, 2015), and has been found to be relevant to the propagation of rumors (Knapp, 1944), front page news (Davis & McLeod, 2003), 'fake news' (Acerbi, 2019), and urban legends (Stubbersfield et al, 2017). As conspiracy theories commonly feature threat-related information, this threat bias has been suggested as a reason for their successful propagation (Stubbersfield, 2021). However, it appears that the threat having its origins in dangerous others is more central to the appeal of conspiracy theories to those high in morbid curiosity than the mere presence of a threat or the nature of what is being threatened (e.g., health or liberty).…”
Section: Discussionmentioning
confidence: 93%
“…This has been demonstrated experimentally using micro-society designs (Blaine & Boyer, 2018;Moussaïd et al, 2015;Stubbersfield et al, 2015), and has been found to be relevant to the propagation of rumors (Knapp, 1944), front page news (Davis & McLeod, 2003), 'fake news' (Acerbi, 2019), and urban legends (Stubbersfield et al, 2017). As conspiracy theories commonly feature threat-related information, this threat bias has been suggested as a reason for their successful propagation (Stubbersfield, 2021). However, it appears that the threat having its origins in dangerous others is more central to the appeal of conspiracy theories to those high in morbid curiosity than the mere presence of a threat or the nature of what is being threatened (e.g., health or liberty).…”
Section: Discussionmentioning
confidence: 93%
“…This has been demonstrated experimentally using micro‐society designs (Blaine & Boyer, 2018; Moussaïd et al, 2015; Stubbersfield et al, 2015), and has been found to be relevant to the propagation of rumours (Knapp, 1944), front page news (Davis & McLeod, 2003), ‘fake news’ (Acerbi, 2019), urban legends (Fessler et al, 2014; Stubbersfield et al, 2017), and international supernatural beliefs (Fessler et al, 2014). As conspiracy theories commonly feature threat‐related information, this threat bias has been suggested as a reason for their successful propagation (Stubbersfield, 2021). However, it appears that the threat having its origins in dangerous others is more central to the appeal of conspiracy theories to those high in morbid curiosity than the mere presence of a threat or the nature of what is being threatened (e.g., health or liberty).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding fake news in general and pseudo-science in particular, it is of great interest to identify specific cultural transmission biases within social media. Acerbi (2019), as well as Stubbersfield (2021), who puts a specific focus on conspiracy theories and modern urban myths, both investigated such biases. In the following, we shall inquire which content biases might help to explain the success of fake news about COVID-19.…”
Section: Cultural Evolutionary Biases and How They Influence The Spre...mentioning
confidence: 99%
“…Since negative fake news affecting survival in the case of the COVID-19 pandemic largely relates to perceived threats (see WHO mythbusters, 2022), "negativity bias" and "threat bias" are presented together here. Acerbi (2019) as well as Stubbersfield (2021) relied on data from two experimental US studies by Fessler et al (2014). They aimed at showing an increased belief in information with negative connotations rather than positive information, even if the content is (ceteris paribus) identical.…”
Section: Content Biases: Negativity Bias and Threat Biasmentioning
confidence: 99%